Optimasi Penggunaan Pupuk Dengan Model Matematika - Gea, Chelsa Julian; Ndruru, Eka Julianti; Lase, Septiani; Laoli, Monica Endang Lestari (Jurnal Ilmu Pertanian dan Perikanan, 2024)
Efficient use of fertilizers is crucial for increasing agricultural yields while maintaining environmental sustainability. This research aims to optimize fertilizer usage through a mathematical model that can describe the relationship between the amount of fertilizer used and the agricultural output achieved. The model employs optimization theory to determine the most effective fertilizer dosage based on various factors such as crop type, soil conditions, and climate. With this approach, it is expected that fertilizer use can be carried out efficiently, reducing waste and minimizing negative environmental impacts. The results of this model can provide recommendations for optimal fertilizer dosages for farmers to improve productivity while considering costs and minimal ecological impact